Sorghum root-system classification in contrasting P environments reveals three main rooting types and root-architecture-related marker–trait associations. (17th January 2018) - Parra-Londono, Sebastian; Kavka, Mareike; Samans, Birgit; Snowdon, Rod; Wieckhorst, Silke; Uptmoor, Ralf
Abstract: Background and Aims: Roots facilitate acquisition of macro- and micronutrients, which are crucial for plant productivity and anchorage in the soil. Phosphorus (P) is rapidly immobilized in the soil and hardly available for plants. Adaptation to P scarcity relies on changes in root morphology towards rooting systems well suited for topsoil foraging. Root-system architecture (RSA) defines the spatial organization of the network comprising primary, lateral and stem-derived roots and is important for adaptation to stress conditions. RSA phenotyping is a challenging task and essential for understanding root development. Methods: In this study, 19 traits describing RSA were analysed in a diversity panel comprising 194 sorghum genotypes, fingerprinted with a 90-k single-nucleotide polymorphism (SNP) array and grown under low and high P availability. Key Results: Multivariate analysis was conducted and revealed three different RSA types: (1) a small root system; (2) a compact and bushy rooting type; and (3) an exploratory root system, which might benefit plant growth and development if water, nitrogen (N) or P availability is limited. While several genotypes displayed similar rooting types in different environments, others responded to P scarcity positively by developing more exploratory root systems, or negatively with root growth suppression. Genome-wide association studies revealed significant quantitative trait loci ( P < 2.9 × 10 −6 ) on chromosomes SBI-02, SBI-03, SBI-05 and SBI-09. Co-localization of significant and suggestive ( P < 5.7 × 10 −5 ) associations for several traits indicated hotspots controlling root-system development on chromosomes SBI-02 and SBI-03. Conclusions: Sorghum genotypes with a compact, bushy and shallow root system provide potential adaptation to P scarcity in the field by allowing thorough topsoil foraging, while genotypes with an exploratory root system may be advantageous if N or water is the limiting factor, although such genotypes showed highest P uptake levels under the artificial conditions of the present study.